Selbständig statt leistungsberechtigt: Eine Implementationsstudie zur Handhabung des Einstiegsgeldes in den Jobcentern - Hans J. Pongratz; Stefan Bernhard; Joachim Wolff; Markus Promberger (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2013)
Der Forschungsbericht präsentiert Ergebnisse einer qualitativen Implementationsstudie zum Umgang mit dem Einstiegsgeld (ESG) in der Gründungsvariante in den Grundsicherungsstellen. Rein deskriptiv betrachtet hat die Zahl der Förderungen mit Einstiegsgeld auf insgesamt geringem Niveau nach der Einführung im Jahr 2005 zunächst einen kleinen Boom erlebt und erreichte in den Jahren 2006 und 2007 jährliche Zugänge von mehr als 32 Tsd. Förderfällen. In Relation zum durchschnittlichen Bestand arbeitsloser erwerbsfähiger Leistungsberechtigter in Höhe von 2,8 Mio. Personen im Jahr 2006 und 2,5 Mio. Personen im Jahr 2007 war die Anzahl der Förderfälle dennoch gering. Seit dem Jahr 2007 hat die Zahl der Eintritte in die Förderung schrittweise nachgelassen, was sich nicht alleine durch einen Rückgang des Bestands arbeitsloser Arbeitslosengeld-II-Bezieher erklären lässt. Auf Grundlage der vorliegenden Studie können wir annehmen, dass der Rückgang der Förderfälle nicht in erster Linie auf ein abnehmendes Interesse von angehenden GründerInnen an der Einstiegsgeldförderung zurückzuführen ist, sondern zumindest teilweise auch auf veränderte Vergabeverfahren in den Grundsicherungsstellen. In der vorliegenden Studie werden drei Handlungsprobleme der Gründungsförderung im SGB II identifiziert... – – This report presents results from a qualitative study on the implementation of a startup subsidy for unemployed welfare recipients (the so-called Einstiegsgeld). Our central findings are: - After the introduction of Einstiegsgeld in 2005 the inflow into the start-up subsidy reached an early peak in the years 2006 and 2007 at more than 32 thousand programme starts annually. In relation to an annual stock of 2.5 to 2.8 million unemployed welfare recipients in these years, the inflow was rather small. Since 2007, there has been a continuous decline of the inflow into the start-up subsidy. This does not only reflect a reduction in the stock of eligible welfare recipients. Based on results of this study we can assume that this development is partly caused by changes of the jobcenters selection processes, which became stricter after their initial experience with the Einstiegsgeld programme. - Within these jobcenters there are three main mechanisms of selecting participants into the programme: (1) The jobcenters decisions depend on the approval of the welfare recipients business plan by external experts. (2) Jobcenters have implemented stepwise selection procedures for granting Einstiegsgeld to welfare recipients. This leads to a relatively high number of voluntary drop-outs and thus reduces the number of applications for the subsidy. (3) Finally, often some case-workers in the jobcenters have gained specialized knowledge on entrepreneurship issues that helps them to guide the process of selecting welfare recipients for the start-up subsidy. - Jobcenters and their employees confront three main problems when they take decisions about granting the subsidy: (1) Assisting the potential entrepreneurs and selecting them for the subsidy is much more complicated and less common than job placements are. Employees face new and challenging tasks, e.g. when it comes to assessing the prospects for success of an envisaged business formation. (2) Due to the fact that the nascent entrepreneurs are welfare recipients and that the start-up subsidy takes place in an institutional context, the relation between jobcenter and potential entrepreneurs is restricted in certain ways. For example, welfare recipients are likely to withhold information that may be relevant for their entrepreneurial undertaking simply because it might threaten their entitlements to benefits. (3) The cooperation of jobcenters with local experts on entrepreneurship is central to the administration of the Einstiegsgeld. However, experts and jobcenters tend to focus strictly on their respective areas of discretion. Thus, each of them misses out part of the story: Jobcenters do not take responsibility for the economic assessment of the experts and the experts do not take into account the fact that their clientele are not only potential entrepreneurs but at the same time welfare recipients. - Since the administration of the Einstiegsgeld is complex and challenging an internal division of labour seems to be an adequate strategy for jobcenters. While all jobcenters have thought about such a specialization at some point in time not all of them made a decision for specializing some of their staff for the handling of Einstiegsgeld. When making their decisions jobcenters have to balance pros and cons: Advantages of specialization are the greater experience and relevant knowledge that specialists possess and that can help to implement Einstiegsgeld effectively. However, specialization may not be appropriate, because of a relatively low number of cases and thus the danger to overinvest organizational resources in a relatively small scheme.
Keywords: 330; Arbeitslosengeld II-Empfänger; Einstiegsgeld; berufliche Selbständigkeit - Förderung; Arbeitsmarktpolitik; arbeitsmarktpolitische Maßnahme; Politikumsetzung; Job-Center; Arbeitsmarktpolitik; Selbstständige; Gründungsförderung; Arbeitsvermittlung; Deutschland